1997
DOI: 10.1007/bf02436077
|View full text |Cite
|
Sign up to set email alerts
|

Protein quality of raw and autoclaved cowpeas: Comparison between some insect resistant and susceptible varieties

Abstract: A comparative study was conducted with four improved cowpea (2 pod bug resistant and 2 susceptible) varieties to assess the effect of autoclaving at 105 degrees C under 15 psi for 30 min on their protein quality, as measured by the levels of some antinutritional factors and performance of rats fed the different cowpea diets. Also, the relationships between antinutrients in the cowpeas and protein quality indicators were examined. Results showed that autoclaving completely eliminated trypsin inhibitor, hemagglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Rats and chickens fed autoclaved faba beans had increased weight gain and greater gain-to-feed ratios compared with those fed control diets. Similar results have been found in cowpea, for which autoclaving at 105°C for 30 min abolished the activity of both trypsin inhibitors and hemagglutinins (Umoren et al 1997). In addition to inactivation of the antinutritive factors, heating is capable of altering the amino acid composition of protein sources, particularly by reducing available lysine content (del Cueto et al 1960;Srihara and Alexander 1983).…”
Section: Factors Influencing Protein Qualitysupporting
confidence: 82%
“…Rats and chickens fed autoclaved faba beans had increased weight gain and greater gain-to-feed ratios compared with those fed control diets. Similar results have been found in cowpea, for which autoclaving at 105°C for 30 min abolished the activity of both trypsin inhibitors and hemagglutinins (Umoren et al 1997). In addition to inactivation of the antinutritive factors, heating is capable of altering the amino acid composition of protein sources, particularly by reducing available lysine content (del Cueto et al 1960;Srihara and Alexander 1983).…”
Section: Factors Influencing Protein Qualitysupporting
confidence: 82%
“…Nell and collaborators 9 found that the true protein digestibility of autoclaved cowpea meal was 76 ± 2.2% which did not differ significantly from 73 ± 2.2% found for untreated cowpea meal. Similar values were reported by Elias et al 10 Cowpea seeds have heat-labile antinutritional substances such as protease inhibitors and lectins 6,11,12 that are responsible for diminishing protein digestibility. 13 However it has been observed that although the heat-treatment of several cowpea cultivars improved some of the nutritional parameters it was not sufficient to promote a regular animal growth when the seed meal was incorporated into diets for rats.…”
Section: Introductionsupporting
confidence: 77%
“…These authors suggested that the presence of antinutritional factors would account for the observed changes. According to a recent study undertaken by Umoren and collaborators, 6 only trypsin inhibitor has a significantly depressing effect on weight gain of rats fed a diet containing raw cowpea, whereas lectin, tannic acid, HCN and phytic acid did not have a significant effect. Hernandez et al 35 attributed the reduced digestibility of cowpea globulin to its higher trypsin inhibitor content over that of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…The animals provided the untreated pinto flour and the untreated buckwheat/pinto blend were unable to complete the study due to feed refusal. This was most likely due to the presence of antinutritive factors present in untreated beans such as proteolytic inhibitors, , hemagglutinins, and tannins, which would have been destroyed or inactivated by the extrusion and baking process. , The amino acid scores for the remaining ingredients are presented in Table . The amino acid score of buckwheat increased after extrusion, with the limiting amino acid remaining leucine.…”
Section: Resultsmentioning
confidence: 99%
“…This system is commonly used in the production of cereals, snacks, and pastas. This process has been shown to have no effect on protein content, , but can alter amino acid composition of beans. Additionally, extrusion can increase protein digestibility of beans, possibly through reducing the activity of trypsin inhibitors. ,, Although there have been few studies determining the effects of baking on plant protein quality directly, the use of autoclaving as a surrogate of heat treatment is relatively common. With autoclaving, a reduction in lysine content of approximately 10% was noted for chickpeas treated for 1 h . A previous investigation of plant protein blends found a significant reduction in lysine content after as little as 5 min of exposure to heating at 121 °C .…”
Section: Introductionmentioning
confidence: 99%